Comparison of hydrogels to enhance the environmental tolerance of the entomopathogenic nematode, Steinernema carpocapsae to target aboveground insect pests such as the lesser peachtree borer (Synanthedon pictipes, (Lepidoptera: Sesiidae)) - Sabrina A. Elgar; David I. Shapiro-Ilan; David Mota-Sanchez; John Wise; Brett R. Blaauw (Biological Control, 2025)
The lesser peachtree borer (LPTB; Synanthedon pictipes; [Grote & Robinson]; (Lepidoptera: Sesiidae) is a key pest of peaches in the southeastern U.S., that develops beneath the bark and is difficult to manage with chemical insecticides. Entomopathogenic nematodes (EPNs) such as Steinernema carpocapsae, offer a potential aboveground biological control option, but their effectiveness is limited by UV exposure and desiccation. In this study, we evaluated the survival (viability) and infectivity (virulence) of S. carpocapsae suspended in five gel treatments, Barricade®, sodium alginate, carboxymethyl cellulose (CMC), xanthan gum, and locust bean gum, as well as water. EPNs were exposed to UV radiation for 0, 3, 6, or 8 h in the laboratory or sprayed onto peach bark and exposed to outdoor conditions for up to three hours. EPN mortality and virulence against Galleria mellonella larvae were assessed post-exposure. Laboratory assays showed that sodium alginate and locust bean gum provided the greatest protection to EPN viability and supported high larval mortality after 6to8 h of UV exposure, comparable to the synthetic gel Barricade®. Outdoor assays revealed that EPNs in these three gels retained higher virulence than those in water, CMC, or xanthan gum after exposure on bark surfaces. Results support the use of natural hydrogels to improve EPN resilience in aboveground environments, promoting their use in sustainable pest management for peach pests. Future research should investigate field applications, including optimal treatment timing and gel degradation dynamics, to optimize natural gels for protecting EPNs in aboveground treatments targeting LPTB larvae and other wood-boring insects.